The Effect of Giving Gamal Leaf Bokashi (Gliricidia Sepium) on Various Depths of Mercury-Contaminated Soil and Its Accumulation in Plant Tissue - Rully Akbar Pribudi Djalalembah (International Journal of Technology and Education Research, 2026)
Mercury (Hg) contamination in soils affected by small-scale gold processing may reduce soil quality and create a pathway for heavy metal transfer into plant tissues. This study assessed the role of kirinyu bokashi (Chromolaena odorata L.) in regulating Hg distribution in contaminated soil and Hg accumulation in maize tissues across different soil depths. The greenhouse experiment was conducted at the Faculty of Agriculture, Tadulako University, using Hg-contaminated soil collected from the Poboya gold-processing area, Palu City. A factorial experiment in a randomized block design was applied with two factors: soil depth (0-10 cm, 11-20 cm, and 21-30 cm) and bokashi dosage (0, 15, 30, and 45 t ha-1). Each treatment combination was replicated three times, resulting in 36 experimental units. Observed variables included soil Hg, plant Hg, plant Hg uptake, soil pH, organic C, and cation exchange capacity. The results indicated that kirinyu bokashi altered Hg distribution in contaminated soil, reduced Hg concentration in plant tissues, and improved selected soil chemical properties, particularly organic C and cation exchange capacity. The 45 t ha-1 treatment showed the strongest tendency to suppress soil and plant Hg, although the magnitude varied among depths. These findings suggest that gliricidia sepium bokashi has potential as an organic amendment for managing Hg-contaminated soil.